PENGARUH PARTISIPASI PENGANGGARAN, ASIMETRI INFORMASI, DAN SELF ESTEEM PADA BUDGETARY SLACK DENGAN BUDGET EMPHASIS SEBAGAI VARIABEL PEMODERASI (Studi Pada Hotel Berbintang di Kota Denpasar) - Cinitya Ardanari, I Gusti Agung Ayu Surya; Asmara Putra, I Nyoman Wijana (E-Jurnal Akuntansi, 2014)
This study outlines the effect of budgetary participation, information asymmetry, and selfesteem on budgetary slack to be moderated by budget emphasis. The population in this study is all star-hotel in the city of Denpasar, while the sample for this study was determined by purposive sampling method. The samples obtained in this study were 12 3-star hotels and above. Respondents of this study were middle-level and lower-level managers who work at the hotel who had been in office for at least one year and included in the budget. From 70 questionnaires that have been distributed, 53 questionnaires have been received and filled correctly. Data are collected after the validity and reliability test and is in compliance classical assumptions are then processed using the Moderated Regression Analysis (MRA) which is a special application of multiple linear regression. The results of this study indicate that budgetary participation and self esteem negatively affect budgetary slack, while the positive effect of information asymmetry on budgetary slack. In addition, budget emphasis was also able to moderate the relationship budgetary participation, information asymmetry, and self esteem on budgetary slack, where budget emphasisweakens the influence of the three.
Keywords: budgetary participation, information asymmetry, self esteem, budget emphasis and budgetary slack.